Caso clínico: síndrome poliglandular autoinmune tipo II, forma de presentación en un paciente adulto - Pereira C., Nicolas; Rau M., Carlos; Araya Q. , Verónica (Revista Hospital Clínico Universidad de Chile, 2008)
Autoimmune Polyglandular Syndrome (APS) type II or Schmidt`s Syndrome is diagnosed when a patient has adrenocortical deficiency with type 1 diabetes mellitus, chronic lymphocytic thyroiditis, or Graves’ disease. The disease commonly manifests in the third or fourth decade. We present the case of a 45 yo male patient who manifested simultaneously at the moment of diagnosis, clinical and laboratory features of hypothyroidism, pernicious anemia and Addison disease. We discuss etiologic, clinical and biochemical aspects in type II APS.